2013
DOI: 10.1111/jpc.12291
|View full text |Cite
|
Sign up to set email alerts
|

Management of children with spinal muscular atrophy type 1 in Australia

Abstract: Aims: To (1) estimate the prevalence of Spinal Muscular Atrophy Type 1 (SMA 1); (2) describe what practices characterise end-of-life care of patients with SMA 1; (3) ascertain whether a consistent approach to the management of these patients exists in Australia. Methods: An audit of the Australasian pathology laboratories offering the diagnostic SMN1 deletion test was conducted for patients diagnosed with SMA in Australia for 2010 and 2011. In addition, a retrospective clinical audit was conducted in eight maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
40
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 23 publications
0
40
0
3
Order By: Relevance
“…One important factor omitted from your otherwise excellent editorial 1 and associated report 2 and review 3 of the ethics of long-term ventilation of infants with spinal muscular atrophy is that death at 1-2 years of age is not accompanied by the patient's comprehension of dying. Dying in infancy is likely to be much less distressing for the patient than when dying is accompanied by awareness later in life.…”
mentioning
confidence: 99%
“…One important factor omitted from your otherwise excellent editorial 1 and associated report 2 and review 3 of the ethics of long-term ventilation of infants with spinal muscular atrophy is that death at 1-2 years of age is not accompanied by the patient's comprehension of dying. Dying in infancy is likely to be much less distressing for the patient than when dying is accompanied by awareness later in life.…”
mentioning
confidence: 99%
“…4,5 In a few countries, children with SMA type 1 are sometimes kept alive indefinitely using artificial ventilation. Our paper questions the ethical justification.…”
mentioning
confidence: 99%
“…6 We submitted an updated report on the child to the JPCH, 4 intending to publish without parental permission. However, new evidence shows Australian children are hardly ever ventilated for SMA type 1, 5 and the reviewers and editor appropriately declined publication without permission, because the child was too readily identifiable. The senior author who is the main carer of the patient then asked the parents' permission, which they gave unhesitatingly.…”
mentioning
confidence: 99%
“…1 Although they have focused upon the negative influences of cross-border media advertising from Thailand, over which health practitioners have little influence, they have also confirmed that initiation of breastfeeding in the first hour after delivery, a factor known from other studies to be important for breastfeeding initiation and for child survival, is one of the significant influences upon exclusive breastfeeding in this population.…”
mentioning
confidence: 99%